2008
DOI: 10.1093/oxrep/grn028
|View full text |Cite
|
Sign up to set email alerts
|

Scale, diversity, and determinants of labour migration in Europe

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
125
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(142 citation statements)
references
References 24 publications
8
125
0
9
Order By: Relevance
“…The level of explanation (R 2 ) was greatest for Stayers -those who have never migrated and do not intend to migrate in future, followed by Roamers, and then Aspirers. The overall level of explanation provided by risk and risk-related competences and motivations is reasonable, or relatively good, compared to many analyses of the determinants of migration (Zaiceva and Zimmermann 2008;van Dalen and Henkens 2012). The distribution of coefficient values confirmed that there are striking contrasts between the four mobility groups in terms of their socio-demographic characteristics, tolerance of risk (general versus mobility-specific risks) and competence to manage risks.…”
Section: Discussionsupporting
confidence: 51%
“…The level of explanation (R 2 ) was greatest for Stayers -those who have never migrated and do not intend to migrate in future, followed by Roamers, and then Aspirers. The overall level of explanation provided by risk and risk-related competences and motivations is reasonable, or relatively good, compared to many analyses of the determinants of migration (Zaiceva and Zimmermann 2008;van Dalen and Henkens 2012). The distribution of coefficient values confirmed that there are striking contrasts between the four mobility groups in terms of their socio-demographic characteristics, tolerance of risk (general versus mobility-specific risks) and competence to manage risks.…”
Section: Discussionsupporting
confidence: 51%
“…Numerous empirical studies have estimated the individual migration decision, consistently concluding that age has a negative impact on the migration probability (see, among others, Bauer and Zimmermann, 1999 for a review; Zaiceva and Zimmermann, 2008). Table 2 reviews the selected studies and presents coefficients of age estimates.…”
Section: B) Empirical Studies With Individual Datamentioning
confidence: 99%
“…Migration had the dominant impact but is the most uncertain determinant of population change. As labour migration has dominated in Europe for decades (Zaiceva and Zimmermann, 2008) it is linked to economic growth and at a deeper level to perceived income disparities, quality of life and migration policy. Increasing Irish fertility rates are anomalously high (Feld, 2005) and seen as unlikely to be maintained.…”
Section: Populationmentioning
confidence: 99%